Comparative Phylogeography of Antarctic Seaweeds: Genetic Consequences of Historical Climatic Variations - Guillemin, Marie-Laure; González-Wevar, Claudio; Cárdenas, Leyla; Dubrasquet, Hélène; Garrido, Ignacio; Montecinos, Alejandro; Ocaranza-Barrera, Paula; Flores Robles, Kamilla (My University, 2020)
In the Southern Ocean, rapid climatic fluctuations during the Quaternary are thought to have induced range contractions and bottlenecks, which drastically impacted marine communities. For photosynthetic macroalgae that are restricted to very shallow waters, survival in deepwater refugia is not possible. Comparing pattern of distribution of genetic diversity using sequences of mitochondrial and chloroplast markers in distinct species of green, brown and red macroalgae, we sought to detect common responses to the effect of these glacial cycles. All the Antarctic macroalgae were characterized by very low genetic diversity, absence of genetic structure and significant signatures of recent population expansion. The eight studied species seem to have barely survived glacial events in situ, in a unique refugium from which they recolonized their current distribution area. We propose that polynyas or areas showing long-term geothermal activity along Antarctic continental margins or peri-Antarctic islands could be good candidate as glacial refugium, but more variable genetic markers will be needed to precisely pinpoint its location. Common haplotypes, scattered over hundreds or even thousands of kilometres of coastline, point out to long-distance dispersal of fronds drifting on the strong oceanic currents in the region as the main mechanism of postglacial expansion.
Keywords: genetic diversity; glacial refugia; last glacial maximum; population bottleneck; quaternary; southern ocean